Robust Speech Recognition Using Factorial HMMs for Home Environments. (14th February 2007) - Betkowska Betkowska, Agnieszka Agnieszka; Shinoda Shinoda, Koichi Koichi; Furui Furui, Sadaoki Sadaoki
Abstract : We focus on the problem of speech recognition in the presence of nonstationary sudden noise, which is very likely to happen in home environments. As a model compensation method for this problem, we investigated the use of factorial hidden Markov model (FHMM) architecture developed from a clean-speech hidden Markov model (HMM) and a sudden-noise HMM. While in conventional studies this architecture is defined only for static features of the observation vector, we extended it to dynamic features. In addition, we performed home-environment adaptation of FHMMs to the characteristics of a given house. A database recorded by a personal robot called PaPeRo in home environments was used for the evaluation of the proposed method. Isolated word recognition experiments demonstrated the effectiveness of the proposed method under noisy conditions. Home-dependent word FHMMs (HD-FHMMs) reduced the word error rate by 20.5% compared to that of the clean-speech word HMMs.